PHARMACOGNOSTIC STANDARDISATION AND PHYSICO-CHEMICAL EVALUATIONS OF LEAVES OF EUGENIA SINGAMPATTIANA BEDDOME ENDANGERED SPECIES - P. PAVENDAN; C. SEBASTIAN RAJASEKARAN; V. ANAND GIDEON (International Journal of Pharma and Bio Sciences, 2011)
The various pharmacognostical parameters of leaf of Eugenia singampattiana Bedd was carried out as per World Health Organization guidelines procedure. Physical constant values involving ash, extractives, Fluorescence, quantitative estimation of various phytochemicals (alkaloid, Anthraquinone, Coumarin, Catechin, Glycoside, Flavonoid, Phenol, Quinone, saponin, steroid, tannin, Terpenoid, Sugar, Xanthoprotein, and Fixed Oil some other chemical constituents are recorded) and morphological features have been recorded. This plant is used for treatment of rheumatism. In order to ensure the use of only genuine and uniform material in preparation of herbal formulation, work on standardization was carried out. The result of the pharmacognostical standardization of this plant serves as a reference piece and helps in future identification and authentication of this plant specimen.